Exploring the influence of ICT on sustainability in supply management: Evidence and directions for research - Pietro Evangelista; Jukka Hallikas (Cleaner Logistics and Supply Chain)
This paper explores the influence of information and communication technology (ICT) adoption on sustainability practices in purchasing and supply management (PSM) as well as its effects on purchasing performance. To accomplish this objective, a comprehensive review of the literature was conducted. The review revealed that little research has been carried out on the effects of digitalization on PSM, the unclear impact of sustainability initiatives on purchasing performance, and the dearth of (empirical) studies concerning ICT, sustainability, and PSM. To address these research gaps, hypotheses were defined and a conceptual framework was tested through a survey involving 131 companies operating in the Finnish economy. The results indicated that both operational and tactical procurement ICT systems positively influence sustainability practices in PSM. Moreover, sustainability practices supported by ICT systems were found to have a positive influence on purchasing performance. This paper differs from previous studies as it suggests a paradigm shift whereby technology is recognized as being integral to sustainability due to their reciprocal relationship, rather than being viewed simply as an enabler or barrier. The study also contributed to the literature by suggesting a novel framework that considers ICT and sustainability in PSM in an integrated way, overcoming the limitations of previous studies that considered them separately.